Integration of Sustainable Governance in Improving the Economy of Coastal Communities Based on Blue Economy in Southwest Papua Province - Rahman, ‎; Ibrahim, Muh Akmal; Musa'ad, Muhammad (KnE Social Sciences, 2025)
To reduce the overexploitation of natural resources and the environment, it is necessary to pay attention to improving the economy of coastal communities based on the blue economy. This research aims to analyze the principle of integration in sustainable governance in improving the economy of coastal communities based on the blue economy in Southwest Papua Province. This research used a qualitative approach. Data collection methods included observation, in-depth interviews, and documentation. Data sources consisted of primary and secondary data, while data analysis was conducted using interactive methods. The informants in this research are stakeholders who are directly involved in improving the economy of coastal communities in Southwest Papua Province. The results show that integration in sustainable governance is realized through collaboration between local governments, traditional institutions, academics, and indigenous peoples in coastal area management. The transdisciplinary approach has begun to be applied by integrating knowledge, local cultural values, and blue economy-based policies. Blue economy-based programs such as sustainable fisheries, ecotourism, and mariculture have been implemented. However, integration still faces problems such as the lack of integrated data, weak coordination between sectors, and limited capacity of indigenous peoples. Nevertheless, the support of the special autonomy policy and the commitment of the local government is one of the key factors in improving the economy of coastal communities based on the blue economy.